Spectroscopic Study on the Species and Color Differences of Gem-Quality Red Garnets from Malawi - Ming Li (Journal of Spectroscopy)
To reveal the species of gem-grade red garnets with similar colors, especially the mechanisms underlying their subtle color differences, a series of tests, including conventional gemological tests, X-ray diffraction, Fourier-transform infrared spectroscopy, ultraviolet-visible spectroscopy, and X-ray photoelectron spectroscopy, were performed on gem-grade red garnets mined from Malawi. The results demonstrated that the color difference is not caused by the difference in species, and both the purplish-red and maroon-red garnets were magnesium-aluminum garnets (pyrope). They both contained the transition metal ions Fe2+, Mn2+, Fe3+, and Cr3+, with Fe2+ and Mn2+ occupying crystal site A and Fe3+ and Cr3+ occupying crystal site B. Cr3+ absorption peaks were observed at 367 and 690 nm; Fe3+ absorption peaks were observed at 502, 528, and 570 nm; and Mn2+ absorption peaks were observed at 400, 423, and 460 nm, which contributed to their respective colors. However, while the maroon-red pyrope had a larger Fe2+/Fe3+ ratio than the purplish-red pyrope, it lacked Mn2+ ions, which is the cause of the color difference between the two pyrope garnets. To date, the study of color differences in red garnets remains a major controversial topic. This study proposed an innovative spectroscopic approach, particularly the combination of ultraviolet-visible spectroscopy and X-ray photoelectron spectroscopy, thus providing a novel methodology for investigating color differences in red garnets.